The Narrative of the City and the Culture of Storytelling in Contemporary Algerian Fiction: “Shurfat Bahar al-Shamal” by Waciny Laredj as a Case Study. - aarab, ahmed (El Omda in Linguistics and Discourse Analysis, 2018)
<section class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-(–header-height)" dir="auto" data-turn-id="fc7ea56e-d26a-420a-bab1-0c0c9a6c0b83" data-testid="conversation-turn-35" data-scroll-anchor="false" data-turn="user"> <section class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:3a29cd02-601b-4407-8a6e-f5070a21f27a-17" data-testid="conversation-turn-36" data-scroll-anchor="false" data-turn="assistant"> <div class="text-base my-auto mx-auto [–thread-content-margin:var(–thread-content-margin-xs,calc(var(–spacing)*4))] @w-sm/main:[–thread-content-margin:var(–thread-content-margin-sm,calc(var(–spacing)*6))] @w-lg/main:[–thread-content-margin:var(–thread-content-margin-lg,calc(var(–spacing)*16))] px-(–thread-content-margin)"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" data-message-author-role="assistant" data-message-id="249a94cf-f16c-445d-b3af-f8cb8ebbbd71" data-message-model-slug="gpt-5-mini"> This research paper aims to engage with certain artistic demands that contemporary Algerian Arabic novels attempt to grasp and reconcile by reshaping the question of the novel in its connection with the urban world, considering the city as a discourse that must be attentively interpreted. On this basis, contemporary Algerian novels, particularly the works of Waciny Laredj, draw on urban discourse as a transformative challenge, closely linked to the creativity of the narrative text. This approach allows the novel to convey its complex issues through a distinctive artistic lens, sensitively perceived by the reader.